2016
DOI: 10.3727/096368915x688263
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Angiogenesis Effects of TGF-β1 and Paracrine Factors Secreted from Human Placental Stem Cells in Response to a Pathological Environment

Abstract: Abnormal angiogenesis is a primary cause of many eye diseases, including diabetic retinopathy, age-related macular degeneration, and retinopathy of prematurity. Mesenchymal stem cells (MSCs) are currently being investigated as a treatment for several such retinal diseases based on their neuroprotective and angiogenic potentials. In this study, we evaluated the role of systemically injected human placental amniotic membrane-derived MSCs (AMSCs) on pathological neovascularization of proliferative retinopathy. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 45 publications
(46 reference statements)
1
56
0
2
Order By: Relevance
“…The hallmark of DR is progressive microvascular disease, in which abnormal proliferation of retinal angiogenesis in DR progression is an important pathological change. Retinal blood vessels normally do not penetrate through the inner limiting membrane, so those vessels that break through the inner membrane can be considered as newly generated vessels of the retina.…”
Section: Discussionmentioning
confidence: 99%
“…The hallmark of DR is progressive microvascular disease, in which abnormal proliferation of retinal angiogenesis in DR progression is an important pathological change. Retinal blood vessels normally do not penetrate through the inner limiting membrane, so those vessels that break through the inner membrane can be considered as newly generated vessels of the retina.…”
Section: Discussionmentioning
confidence: 99%
“…There are no effective measures to promote nerve repair after DR nerve damage, and exogenous cell replacement therapy may be a potential treatment for the damage 9 . NSCs have become a promising source of stem cell-based regenerative therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [121] and Zhao et al [122] revealed that the area of retinal neovascularization was significantly smaller in OIR mice with intravitreally injected BM-MSCs on postnatal day 12; the injected MSCs were located in retinal neovascularized areas but did not integrate into the vascular network. Kim et al [123] showed that human placental amniotic membrane-derived MSCs (AM-MSCs) secreted high levels of TGF-β1 and suppressed endothelial cell proliferation under pathological conditions in vitro. Moreover, TGF-β1 siRNA nullified the benefits of MSCs both in vivo and in vitro; TGF-β1 is a key secretory factor in the regulation of MSC-mediated angiogenesis [123].…”
Section: Msc-derived Secretomes For Ropmentioning
confidence: 99%
“…Kim et al [123] showed that human placental amniotic membrane-derived MSCs (AM-MSCs) secreted high levels of TGF-β1 and suppressed endothelial cell proliferation under pathological conditions in vitro. Moreover, TGF-β1 siRNA nullified the benefits of MSCs both in vivo and in vitro; TGF-β1 is a key secretory factor in the regulation of MSC-mediated angiogenesis [123]. Another study described the protective effects of human BM-MSC-derived exosomes against ROP [76].…”
Section: Msc-derived Secretomes For Ropmentioning
confidence: 99%